Some Fresh Water Red and Yellow-Green Algae fom North-Eastern Uttar Pradesh, India - Srivastava, Anand Kumar; Mishra, P. K. (Ecoprint: An International Journal of Ecology, 2016)
Available with fulltext. Key words: Algae; Rhodophyceae; Xanthophyyceae; N.E.U.P. Ecoprint An International Journal of Ecology Vol. 14, 2007 Page: 97-100 Uploaded date: 1 June, 2011